Relatively preserved functional immune capacity with standard COVID-19 vaccine regimen in people living with HIV - Hung, Chen-Yiu; Hsiao, Sung-Han; Huang, Chung-Guei; Chang, Chia-Shiang; Chen, Guan-Yan; Huang, Yu-Lin; Dutta, Avijit; Huang, Ching-Tai (Frontiers in Immunology, 2023)
Introduction: People living with HIV (PLWH) are at a higher risk of sever disease with SARS-CoV-2 virus infection. COVID-19 vaccines are effective in most PLWH. However, suboptimal immune response to the standard 2-shot regimen is a concern, especially for those with moderate to severe immunodeficiency. An additional dose is recommended as part of the extended primary series in Taiwan. Herein, we study the efficacy of this additional shot in PLWH with mild immunodeficiency compared to that in healthy non-HIV people.Methods: 72 PLWH asymptomatic or with mild immunodeficiency (CD4 counts >200/mm³) and suppressed virology, and 362 health care workers of our hospital were enrolled. None of the participants had a history of SARS-CoV-2 infection. They received mRNA-1273 and ChAdOx1 vaccines. Anti-SARS-CoV-2 neutralizing and anti-Spike IgG antibodies, and SARS-CoV-2-specific T cell responses were evaluated.The standard 2-shot regimen elicited lower responses in PLWH than the health care workers without HIV infection, although the difference was statistically insignificant. They have comparable levels of neutralizing and anti-Spike antibodies and comparable effector CD4+ and CD8+ T cell responses. The 3rd shot boosted the SARS-CoV-2 immunity significantly more with better antibody responses and higher IFN-gamma and IL-2 responses of the CD4+ and CD8+ T cells in PLWH compared to the non-HIV people. Upon in vitro stimulation with extracted Wuhan strain SARS-CoV-2 proteins, CD8+ T cells from PLWH after 3 shots has more durable effector responses than the non-HIV controls with extended time of stimulation.This subtle difference between PLWH and non-HIV people implied immune exhaustion with two shots in non-HIV people. Slightly compromised immunity in PLWH indeed preserved the functional capacity for further response to the 3^rd shot or natural infection.